Edugreen: a tree planting initiative and planting plans for elementary school sites in Manhattan, KS - Cheng, Jia (Kansas State University, 2022)
Trees within a schoolyard landscape can directly benefit students—improving their physical, social, mental, and emotional health. Trees also provide significant environmental and economic benefits. When planted near playgrounds and activity areas, the shade cast from trees can help lower surface temperatures and provide enjoyable places to rest. An analysis of existing trees at eight elementary schools in Manhattan, KS, revealed a noticeable absence of trees within the schoolyard landscapes and a significant lack of shade for playground and activity areas. The USD 383 Manhattan-Ogden District provides landscape maintenance of the schoolyards. However, their resources for tree planting and care are limited. Yet, the need for more trees within these schoolyards is critical. Thus, this project explores how a district-wide tree planting initiative can be created to guide and increase tree planting at individual elementary school sites. A detailed tree inventory and site analysis was used to fully understand the existing conditions and to explore future opportunities for new trees at all eight sites. To learn what notable organizations and districts across the country are doing to increase trees at schools, a precedent study of school-based tree planting initiatives was done to reveal best practices for program administration and implementation. Additionally, a survey was sent to the principals of the eight schools to capture their perceptions and awareness about trees at their schoolyards. Findings from these methods helped to inform and structure the proposed Edugreen Tree Planting Initiative. The 5-year initiative illustrates the necessary steps needed to increase tree plantings at each school. A total of 137 trees are proposed. A species list and tree planting plan with annual goals and planting priorities is included for each school. Ultimately, for this district-wide tree planting initiative to succeed, the support of many dedicated individuals is needed. These individuals must champion and oversee tree implementation and ongoing maintenance at each school. The benefits of implementing the initiative will include increased shade, environmental education, and reduced maintenance efforts from the district maintenance department.
Keywords: Schoolyard tree planting; Community stewardship; Tree planting initiative; Environmental education; Green schoolyard